Does the leader's ethnicity matter? Ethnic favoritism, education and health in Sub-Saharan Africa - Raphaël Franck; Ilia Rainer (Bar-Ilan University, Department of Economics, 2012)
In this paper we reassess the role of ethnic favoritism in Sub-Saharan Africa. Using data from 18 African countries, we study how primary education and infant mortality of ethnic groups were affected by changes in the ethnicity of the countries' leaders during the last fifty years. Our results indicate that the effects of ethnic favoritism are large and widespread, thus providing support for ethnicity-based explanations of Africa's underdevelopment. We also conduct a crosscountry analysis of ethnic favoritism in Africa. We find that ethnic favoritism is less prevalent in countries with one dominant religion. In addition, our evidence suggests that stronger fiscal capacity may have enabled African leaders to provide more ethnic favors in education but not in infant mortality. Finally, political factors, linguistic differences and patterns of ethnic segregation are found to be poor predictors of ethnic favoritism.
Keywords: 330; Ethnische Diskriminierung; Allgemeinbildung; Kindersterblichkeit; Regierungswechsel; Regierungschef; Ethnische Gruppe; Afrika südlich der Sahara